Koping Religius pada Santri Difabel Tunadaksa - Aliyah, Nur Anifatul; Riadi, Dela (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2025)
This study aims to explore religious coping strategies among physically disabled students. A qualitative research method with a phenomenological approach was employed to gain a deep understanding of the participants’ lived experiences. The subject of the study was a physically disabled adolescent residing in an Islamic boarding school. Data were collected through in-depth interviews and observations, and the validity of the findings was ensured using triangulation techniques. The results indicate that the subject was able to acknowledge and accept their physical condition. The religious coping strategies identified include the deferring approach, characterized by surrender and trust in divine assistance, and the collaborative approach, in which the subject sought meaning from adversity and actively attempted to resolve problems with reliance on God’s help. Additionally, the subject demonstrated positive religious coping, reflected in attitudes of patience, gratitude, and sincerity. The findings also highlight the importance of social support, with the strongest support coming from parents, followed by peers and the surrounding environment